Tax Evasion and the Social Influence Perspective: A Conceptual Model for Palestine - Abdul-Jabbar, Hijattulah; M. J. Abuamria, Faeyz; Abdallah Alkhatib, Amjad; Marimuthu, Munusamy (International Journal of Psychosocial Rehabilitation, 2020)
Tax evasion is a universal phenomenon that challenges every government worldwide. The purpose of this paper is to propose a conceptual model for understanding factors influencing tax evasion that can be used to study and address tax-related challenges. The proposed model is built upon a review of tax studies from behavioural aspects, particularly the social influence perspective. The current review identified four key variables that likely influence tax evasion behaviour of taxpayers. The variables are: corruption, fairness, ethics, and peer influence. The present model adds to the existing body of tax knowledge from behavioural perspectives. As the compliance behaviour is dependent on individual taxpayers, behavioural factors should be given serious consideration compared to economic factors, as the former is highly dynamic in nature and change over time. In a country like Palestine, with a high level of uncertainty, the proposed behavioural framework from a social influence perspective would benefit tax administrators in understanding and mitigating the tax evasion phenomenon.